Investigating the Patterns of Social Network Sites (SNS) Usage among Business Students - Wan Isa, Wan Malini; Mohd Tahir, Izah; Hassan, Hasni; Rozaimee, Azilawati (2012)
The objective of this paper is to examine the patterns of Social Network Sites (SNS) usage among business students in one of the public university in Malaysia. A total of 327 business students from the Faculty of Business Management and Accountancy participated in the survey. The results indicate that majority of the respondents owns a notebook and use their own notebook to access the internet. In addition, majority of the respondents rated Facebook as their favourite SNSs account and have more than one SNSs account with majority of them are members of Facebook. Regardless of gender, business students used SNSs mainly for chatting.